Sustainable Development of Inland Waterways Transport in Vietnam : Strengthening the Regulatory, Institutional and Funding Frameworks - World Bank (Washington, DC, 2022)
Vietnam has a long history of using its rivers and canals for transportation of goods and people. Today, Vietnam’s waterways transport about 17 percent of all domestic goods tonage loaded in Vietnam and perform nearly 19 percent of all traffic tasks, a measure which combines both tonnes loaded and distance carried. These are very high levels by international standards, and Vietnam’s national freight task proportion is more than double that for China, the United States, and the European Union where inland waterways are also prevalent. Right after its integration into the international economic community in the late 1980s, Vietnam listed the development of inland waterways transport as one of its priorities to boost economic growth. Overcoming financing constraints, the country has made enormous strides in developing its inland waterways transport by efficiently exploiting the natural conditions of its rivers and canals. However, exploiting only the natural conditions of Vietnam’s inland waterways could diminish the country’s competitive advantage over time. In order to bring the waterways’ great potential into reality, further investment is required in the institutional structure, in strengthening the legal and regulatory framework, and in improvement of the funding framework for the sector. This report provides a comprehensive review and assessment of the challenges that the sector faces, along with a reform program recommended to the government of Vietnam that could help improve the enabling environment for the inland waterways transport industry and further its growth and technical sophistication.